Helicobacter pylori Eradication Lowers Serum Asymmetric Dimethylarginine Levels - Selim Aydemir; Hacı Eren; Ishak Ozel Tekin; Ferda Akbay Harmandar; Nejat Demircan; Mehmet Cabuk (Hindawi Limited, 2010)
Introduction. Microbial pathogens, one of them is Helicobacter pylori (H. pylori), have frequently been implicated in the atherogenesis. Endothelium-derived nitric oxide (NO) is synthesized from L-arginine by nitric oxide synthase (NOS) and plays a pivotal role in the regulation of vascular tone. Asymmetric dimethylarginine (ADMA) is the most potent endogenous NOS inhibitor. Elevated levels of ADMA have been reported in many circumstances associated with a high cardiovascular risk. The aim of the present study was to investigate whether the eradication of H. pylori infection affects serum ADMA levels. Materials and Methods. Forty-two H. pylori-positive patients were enrolled in the study. Triple therapy for 14 days were given to all patients. Serum ADMA levels were measured at baseline and 2 months after therapy. Results. Eradication was achieved in 34 (81%) patients. The mean serum ADMA levels before and after therapy were 1,77±0,30 and 1,67±0,29 ng/mL in the group with H. pylori eradicated and 1,63±0,28 and 1,56±0,32 ng/mL in the noneradicated, respectively. We detected statistically significant decreased serum ADMA levels after therapy in H. pylori eradicated group. Conclusion. These findings have indicated that eradication of H. pylori infection may decrease the risk of atherosclerosis and cardiovascular events.